SOSIALISASI PENGELOLAAN SAMPAH TERHADAP PENINGKATAN KUALITAS HIDUP BERSIH DI PONDOK PESANTREN NIDHOMUDDIN: Socialization Of Waste To Improve The Quality Of Clean Life In Pondok Pesantren Nidhomuddin - Hasrul Anwar; M. Ridho Ulya; Rizka Mayasari; Akhmad Dzahwan (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Garbage that is not managed properly will cause pollution to water, soil and air pollution. Garbage is often a worthless item, causing no awareness of the existence of this waste. Pondok Pesantren Nidhomuddin, Negara Ratu Natar Village, South Lampung fosters approximately 140 students consisting of 60 male students and 80 female students. Pondok Pesantren Nidhomuddin have facilities such as 1 mosque, 7 classes each for male and female students, 10 bathrooms for male students and 18 bathrooms for female students. Based on the problems above, this activity was carried out to provide solutions to the problems faced by students in Pondok Pesantren Nidhomuddin. This service activity was carried out at Pondok Pesantren Nidhomuddin,Negara Ratu Natar Village, South Lampung. the steps of the community service activities carried out are preliminary studies and location surveys, mapping problems related to organic and organic waste processing, socialization activities and assistance related to organic waste management using the composting method and the ecobrick method for inorganic waste. The material presented in the socialization activity is related to what is organic and inorganic waste, waste processing procedures, organic and inorganic waste processing, environmental sanitation, and finally giving questionnaires at the beginning and end of the workshop activity to evaluate community service activities. Based on the results of the questionnaire given to the socialization participants, there was an increase in the knowledge of the students regarding waste management and environmental sanitation. It is hoped that the students can implement good and correct waste processing in Pondok Pesantren Nidhomuddin.